Learning Agility as a Mediating Mechanism between Self-Efficacy, Locus of Control, and Employee Performance - Nova Pratami NW,; Arief Subyantoro,; R. Heru Kristanto HC, (Technium Social Sciences Journal, 2026)
This research examines the relationship between self-efficacy and locus of control in shaping employee performance within a regional development banking environment, with learning agility positioned as an intervening mechanism. Using a quantitative approach, the research involved all 50 employees of the credit division, selected through a saturated sampling technique. Data were obtained via a structured Likert-scale questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS version 3.2.9. The results reveal that self-efficacy contributes significantly to employee performance at Bank BPD DIY, Wates Branch, whereas There is a positive and insignificant influence of the locus of control on employee performance at Bank BPD DIY, Wates Branch. However, when mediated by learning agility, both self-efficacy and locus of control exhibit significant positive indirect influences on performance at Bank BPD DIY, Wates Branch. These findings highlight the strategic role of learning agility in strengthening human resource effectiveness within regional banking institutions.